Dauru Ta'lim Qawaid al-Lughah al-Arabiyah Fi Bina'i Maharat al-Qira'ah Li al-Tullab al-Faslh al-Awwal Fi Madrasah Hikmah al-Syarif al-Aliyah Nahdlah al-Wathan Salut Narmada Lombok Barat Nusa Tenggara Barat - Fathul Maujud; Cipta Ningsih (Institut Agama Islam Negeri Curup, 2019)
Specifically, this study discuss about Qowaid role in Arabic Language in forming reading skill in student class I Senior High School Hikmatussyarif Nahdhotul Wathan Salut Narmada West of Nusa Tenggara. Significances of this article is to know instruction process Qowaid of Arabic Language and to forming reading skill in student Class I Senior High School Hikmatussyarif Nahdhotul Wathan Salut Narmada West of Nusa Tenggara. As for research study method in this article use Qualitative method, Qowaid instruction has done it well according to effective steps because existence of some components of teacher instruction, student, hand book, material, time, instruction strategy, instruction media and evaluation. And Qowaid instruction has seen from student skill, they have come up with the target of study which have been determined, they read some Arabic references without harakat and also they can write it well.